A fresh insight on measuring energy productivity and environmental performance incorporating health. (1st December 2021) - Wang, Baohui; Qu, Jingjing; Liu, Xiaohong
Abstract: To promote sustainability, it is necessary to consider economic growth, environmental protection and health promotion in a unified framework. Following this line of research, this study addresses three methodological difficulties: (a) how to incorporate health variables into DEA, (b) how to incorporate the potential impact of health variables on labor force participation, and (c) how to evaluate the performance of subsystems. To this end, this study proposes three types of DEA models to explore abatement capacity, the extent of damage to public health and efficiency growth. Empirically, our approaches are utilized to examine Chinese provinces during 2009–2017. The main conclusions are summarized as follows. First, significant differences have been confirmed among three models, suggesting that the choice of models is important for the empirical studies. Second, the eastern region has the more outstanding performance in energy productivity and abatement capacity than the other regions. Finally, the maximum possible inpatient rate in the majority of provinces has been increasing every year, except for Shanghai, Guizhou and Ningxia, due to the influence of each other. Graphical abstract: Image 1 Highlights: This study proposes two types of Data Envelopment Analysis (DEA) models. This study incorporates the potential effect of health on labor. It proposes the maximum possible inpatient rate and the efficiency growth. Our approach is used to examine Chinese provinces. A growing health damage is confirmed among Chinese provinces.